Interference Management for VLC Indoor Systems based on Overlapping Field-of-View Angle Diversity Receivers - Al-Sakkaf, Ahmed Gaafar Ahmed; Morales-Cespedes, Maximo (IEEE access, 2024)
The integration of visible light communications (VLC) in future generation of wireless communications leads to consider the deployment of multiple access points (APs) transmitting in the optical domain. Since each optical AP generates a small and confined coverage footprint, scenarios comprising multiple optical APs are subject to intercell interference. In this context, angle diversity receivers (ADRs) composed of multiple photodiodes pointing to distinct orientations each, have been proposed for mitigating the interference and blocking effects. The design of ADRs typically assumes that the field-of-view (FoV) generated by each photodiode does not overlap with the FoV of all other photodiodes. In this work, we propose the derivation of the theoretical expressions of the probability distribution function (PDF) and the cumulative distribution function (CDF) of the signal-to-interference plus noise ratio (SINR) in multicell scenarios for ADRs in which the FoV generated by each photodiode may overlap with the FoV of the other photodiodes. Several geometrical conditions are proposed in order to derive the statistical characterization of photodiode combining schemes such as select best combining (SBC), equal gain combining (EGC) and maximum ratio combining (MRC). It is shown that the derived closed-form expressions obtain a similar performance as the results obtained through Monte Carlo simulations. Moreover, the SINR enhancement due to the use of the proposed ADR in comparison with single photodiode receivers is highlighted.